ZmHOX32 is related to photosynthesis and likely functions in plant architecture of maize - Miao, Xinxin; Zhu, Wanchao; Jin, Qixiao; Song, Zemeng; Li, Lin (Frontiers in Plant Science, 2023)
HOX32, a member of the HD-ZIP III family, functions in the leaf morphogenesis and plant photosynthesis. However, the regulatory mechanism of HOX32 in maize has not been studied and the regulatory relationship in photosynthesis is unclear. Here, we analyzed the phylogenetic tree of ZmHOX32 and found it shows conservation in plants. As expected, maize HOX32 protein is specifically expressed in the nucleus. ZmHOX32 showed constitutively expression at both transcriptome and translatome levels. We uncovered the downstream target genes of ZmHOX32 using tsCUT&Tag and constructed a cascaded regulatory network combining the co-expression networks. Both direct and indirect targets of ZmHOX32 showed significant gene ontology enrichment in terms of photosynthesis in maize. The association study suggested that ZmHOX32 plays an important role in regulation of plant architecture. Our results illustrate a complex regulatory network of HOX32 involving in photosynthesis and plant architecture, which deepens our understanding of the phenotypic variation in plants.